Psychological Aspects experienced by high performance athletes during the period of social isolation: an exploratory study (Research, Society and Development, 2022)
The Covid-19 pandemic impacted hundreds of high-performance athletes whose reflexes were present not only during the period of social isolation, but also after returning to in-person activities. Given the changes in practice and routine resulting from the pandemic, this study sought to understand the perception of athletes about this experience. The sample consisted of 10 athletes from the field soccer modality, five from the under 17 category and five from the under 20 category. A sociodemographic questionnaire and semi-structured interview were used. From the content analysis, the results indicated that the athletes perceived difficulties such as: performing the tasks of sports practice (space at home, training alone, keeping the focus and activities routine), adjusting to changes and experiencing feelings of emotional distress ; however, resting with the family, adapting to the new conditions proposed by social isolation, engaging in free-time activities, feelings about valuing personal and professional life were aspects identified as positive. Apparently, the athletes were adjusting psychologically, managing their sports routine better and introducing new free time activities throughout the pandemic period, especially due to the support offered by the club and multidisciplinary team. Such knowledge can be used as a basis for the development of prevention projects in the face of psychological vulnerabilities arising from the social isolation experienced by high-performance athletes, as well as helping psychology professionals to adjust interventions aimed at athletes who experience similar situations.